OPTIMIZATION OF THE IMPLEMENTATION OF MANDATORY HOUSING SAVINGS TO PROVIDE AFFORDABLE HOUSING FOR INDONESIAN NATIONAL ARMY SOLDIERS - Rambe, Muntara; Yazdi Martin, Abraham; Sihotang, Sudiman (Fakultas Hukum Universitas Djuanda, 2024)
In order to meet the housing needs of soldiers, the TNI collaborates with the State Savings Bank (BTN) regarding the management of self-managed housing mortgages. For this KPR scheme, BTN allocates distribution realization of around 7,000-8,500 units per year, and BTN allocates distribution realization between 1,500-3,000 units per year for the TWP AD KPR program. On the one hand, this program is a solution to meeting housing needs for TNI soldiers, but on the other hand it creates new problems for TNI soldiers who have to support their families' needs. The aim of this research is to optimize the form of implementing mandatory housing savings to provide affordable housing for Indonesian National Army Soldiers. This research is used the juridical-normative approach or statutory approach, data analysis is carried out qualitatively, namely by explaining the relationship between legal facts and legal rules contained in statutory regulations. The results of the research show that the mandatory housing savings program is not optimal for providing affordable housing for TNI soldiers and can be optimized by increasing the salaries of TNI soldiers, building flats on land belonging to TNI knights, the one who builds flats for the TNI is the TNI itself, namely Zeni, the highest leader. The TNI needs to negotiate with the DPR-RI to obtain land from the government in order to obtain land allocation from the government for the purpose of building houses for soldiers.